New Ethical Issues in Cerebral Palsy - Dan, Bernard (Frontiers in Neurology, 2021)
Current societal and technological changes have added to the ethical issues faced by people with cerebral palsy. These include new representations of disability, and the current International Classification of Functioning, Disability and Health, changes in legislation and international conventions, as well as applications of possibilities offered by robotics, brain-computer interface devices, muscles and brain stimulation techniques, wearable sensors, artificial intelligence, genetics, and moire for diagnostic, therapeutic or other purposes. These developments have changed the way we approach diagnosis, set goals for intervention, and create new opportunities. This review examines those influences on clinical practice from an ethical perspective, and highlights how a principled approach to clinical bioethics can help the clinician to address ethical dilemmas that occur in practice. It also points to implications of those changes on research priorities.